IRRIGATION SERVICES AND LAND REHABILITATION MEASURES MUTUAL BINDER EFFICIENCY INDICATORS - Iminov Tukhtasin Nurmamatovich; Kurganov Hakimjon Rustamovich; Asilbek Alikhonov Abdullo ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article emphasizes that organizations engaged in irrigation services and reclamation activities on irrigated lands should take into account their specific features in the process of planning, design and effective use of these services and activities. Based on the views of foreign and domestic scientists, indicators have been developed that link irrigation services and land reclamation.